Intercropping of Indian basil (Ocimum basilicum L.) for enhancing resource utilization efficiency of aromatic grasses - D D Patra, S P S Khanuja, Saudan Singh, Aparbal Singh, U B Singh, (Journal of Spices and Aromatic Crops, 2004)
Field trials on interctopping of Indian basil (Ocimum basilicum) with perennial aromatic grasses such as palmarosa (Cymbopogon martinii), lemongrass (Cymbopogon flexuosus) and vetiver (Vetiveria zizanioides) were conducted at Lucknow (Uttar Pradesh). Indian basil was intercropped with aromatic grasses (spaced at 45 cm) during planting and establishment year of aromatic grasses. Intercropping with Indian basil did not affect the essential oil production of aromatic grasses; however oil yield of Indian basil were reduced by 60% and 24% with palmarosa and lemongrass, respectively, over monocropping. Intercropping however, improved the net economic returns of lemongrass, vetiver and palmarosa by 61 %, 140% and 65%, respectively, over their respective monocropping. Intercropping led to considerable improvement in land equivalent ratio 0.36-1.91), area time equivalent ratio (1.04-1.19), land use efficiency 020%-151 %) and money equivalent ratio 0.37-3.01).